PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEB BLOG PADA KONSEP MOMENTUM DAN IMPULS - Udik Prasetyo; Irnin Agustina Dwi Astuti; Dasmo Dasmo; Iman Noor (UNIVERSITAS INDRAPRASTA PGRI, 2020)
A research on development of learning media based on web blogs on the concepts of momentum and impulse has been done. This research aims to determine the feasibility of physics learning media based on web blogs. Method of this research is Research & Development (R&D) with ADDIE model. This learning media is validated by media experts and material experts. Based on the results of the research, development of learning media based on web blogs on the concepts of momentum and impulse is feasible for students to physics learning.